2018
DOI: 10.1590/1678-992x-2016-0407
|View full text |Cite
|
Sign up to set email alerts
|

Common resistance to Fusarium head blight in Brazilian wheat cultivars

Abstract: Mycotoxin levels in Fusarium head blight (FHB) infections can be difficult to quantify.The relationship between mycotoxin and disease is not consistent and it is not clear if wheatpathogen interaction is of significance in regions where more than one Fusarium species with distinct trichothecene production ability co-exists. This study aimed to investigate whether a set of eight Brazilian wheat genotypes, varying in resistance according to classification by the breeder, exhibit a common or differential resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
(39 reference statements)
6
12
0
Order By: Relevance
“…We found that the species with the DON chemotype were generally more aggressive (higher area under severity curve) than the NIV ones, which is in agreement with our previous studies (Mendes et al 2018; Spolti et al 2012a). We could not compare statistically the effect of cultivar because the experiments were conducted at different times, and with different total time duration of the evaluations.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that the species with the DON chemotype were generally more aggressive (higher area under severity curve) than the NIV ones, which is in agreement with our previous studies (Mendes et al 2018; Spolti et al 2012a). We could not compare statistically the effect of cultivar because the experiments were conducted at different times, and with different total time duration of the evaluations.…”
Section: Discussionsupporting
confidence: 93%
“…We could not compare statistically the effect of cultivar because the experiments were conducted at different times, and with different total time duration of the evaluations. Nevertheless, the area under the curve was in general higher for BRS 194, the susceptible one, compared with BRS Guamirim as shown earlier (Mendes et al 2018; Spolti et al 2012a). For the first time, we compared the two acetylates of DON within the Brazilian strains; while 15-ADON ( F. graminearum ) was the most aggressive in a susceptible cultivar, the 3-ADON ( F. austroamericanum ) was the most aggressive in the moderately resistant cultivar.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It is possible that the stock suspension may either need dilution to reach the wanted conidium concentration (such as 5 × 10 5 conidia/mL) or must be concentrated when its density is too low. No details were given in the literature [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], with the expression “adjusted” used in most cases. It appears that the researchers did not think that this practice could influence experimental results.…”
Section: Introductionmentioning
confidence: 99%